Analysis of dose distribution in organs at risk in patients with prostate cancer treated with the intensity-modulated radiation therapy and arc technique - Michal Biegala; Adam Hydzik (Journal of Medical Physics, 2016)
This study describes a comparative analysis of treatment plans in 48 patients with prostate cancer treated with ionizing radiation. Each patient was subjected to the intensity-modulated radiation therapy (IMRT) and arc technique. In each treatment plan, the organs at risk were assessed: the urinary bladder, rectum and heads of the femur, as well as the volume of normal tissue. The following features were compared: treatment time, conformity indices for the planning target volume, mean doses and standard deviation in organs at risk, and organ volumes for each particular dose. The treatment period in the arc technique is 13.7% shorter than in the IMRT technique. Comparing the results of the IMRT and arc techniques (arc vs. IMRT), the mean values were 29.21 ± 12.91 Gy versus 28.36 ± 13.79 Gy for the bladder, 20.36 ± 3.16 Gy versus 18.17 ± 5.11 Gy for the right femoral head, and 18.98 ± 3.28 Gy versus 16.67 ± 5.15 Gy for the left femoral head. For the rectum, lower values were obtained after application of the arc technique, not the IMRT technique: 35.84 ± 12.28 Gy versus 35.90 ± 13.05 Gy. The results indicate that the applied therapy has a statistically significant influence on the volume for a particular dose with regard to the urinary bladder. It is advisable to apply the IMRT technique to patients who need the femur heads and urinary bladder protected by exposing them to low irradiation doses.